Autorreferencialidade narrativa: um estudo sobre estratégias de complexificação na ficção televisual - Capanema, Letícia Xavier de Lemos (2016)
This research investigates the television narratology starting from the fact that the fictional production in television has become more complex in recent decades. Considering that the phenomenon of fiction complexity manifests in a distinct sort of supports (oral, scenic, book, cinematic, televisual or hypermedia), what are the features that allow certain works to be classified as complex narratives? There would be an underlying logic that guide and connect them? This thesis holds the hypothesis that there is a fundamental logic of complex narrative permeating all its concrete manifestations: the self-referentiality, namely, the movement of turning back on itself, generating a metareflective reception by the public. Therefore, the specific objective is to investigate the relationship between the complex narrative and the selfreferentiality, as well as its mechanisms and effects in television studies. The main objective of this thesis is to achieve a precise concept of narrative complexity in fiction television that contributes to the solidification of its narratology. The theoretical object of this study is the notion of complex narrative and the empirical object are the manifestations of the narrative complexity in literary fiction, filmic fiction and especially the televisual fiction. The corpus is the american TV series Twin Peaks. In order to clarify some specific concepts, other television programs are briefly examined. Our methodological procedure relies both on Paul Ricoeur's mimetic circle model and on the narratology of Genette, adapted by André Gaudreault and Francois Jost for audiovisual application. Our theoretical argument about the relationship between the complex narrative and the self-reference is based on Alfonso Romano de Sant'Anna and several other authors who also analyzed self-reference in literature, film and television. The principle of self-referentiality, its types, modes and performance levels are explored based on the approaches of Werner Wolf and Winfried Nöth. The results achieved in this study allow us to conclude that the complex narrative is a phenomenon resulting from self-referential strategies present in instances of content, structure and the narrative act